THE INFLUENCE OF PROFITABILITY, DEBT TO EQUITY RATIO, FIRM SIZE, INNOVATION, AND TIME DISCOUNTING TO DIVIDEND PAYOUT RATIO (Case Study on Manufacturing Companies Listed on Indonesia Stock Exchange 2012-2017) - Rifqi, Ammar; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2018)
This research aims to analyze the influence of Profitability, Debt to Equity Ratio, Firm Size, Innovation, and Time Discounting to Dividend Payout Ratio on the company which sector in manufacturing companies listed in Indonesian Stock Exchange in period 2012-2017.This research used secondary data with population consists of 154 manufacturing companies listed in Indonesia Stock Exchange in the period of 2012-2017. The purposive sampling method used was used in selecting the research sample and 22 manufacturing companies that consistently distributed dividends during the research period. The data used in this research were obtained from the Indonesian Capital Market Directory (ICMD) 2012-2017, Bloomberg, IDX Annual Report, and www.idx.co.id. Analysis technique used Ordinary Least Square Regression (OLS), statistical t-test, f-test, and classic assumption test that includes a test of normality test, multicollinearity test, autucorrelation test, and heteroskedastisitas test.The result of the research are independent variables simultaneously (F test) effect on Dividend Payout Ratio with a significance level of 0.000. While partially (t test) showed that the variable Free Firm Size and Innovation have positive and significant effect on Dividend Payout Ratio. Variable Debt to Equity Ratio and Time Discounting have negative and significant effect on Dividend Payout Ratio. Profitability has positive and not significant effect on Dividend Payout Ratio. Adjusted R2 is 0,294 which means that the ability of the five independent variables can explain Dividend Payout Ratio amounted to 70,6%, while the rest is explained by other factors